Transtrochanteric approach can provide better postoperative care and lower complication rate in the treatment of hip fractures - Gursoy S (Dove Medical Press, 2019)
Safa Gursoy,1 Mehmet Emin Simsek,2 Mustafa Akkaya,1 Metin Dogan,1 Murat Bozkurt1 1Department of Orthopedics and Traumatology, Ankara Yildirim Beyazit University, Ankara 06800, Turkey; 2Department of Orthopedics and Traumatology, Yenimahalle Training and Research Hospital, Ankara 06370, Turkey Purpose: Dislocation is an important complication that increases the mortality, morbidity, and postoperative care following bipolar hemiarthroplasty. It is thought that the transtrochanteric approach that enables access to the femoral neck directly from the fracture line at the coronal plane of the greater trochanter without opening the posterior and anterior capsules could reduce the risk of dislocation. Additionally, it is argued that preservation of the external rotators could also be advantageous for patient rehabilitation and muscle strength. The aim of this study is to compare the effectiveness of the standard posterolateral approach and transtrochanteric approach performed from the fracture line, primarily the rate of dislocation, in osteoporotic Evans Type IV–V unstable intertrochanteric fractures on which bipolar hemiarthroplasty was performed. Patients and method: One hundred and twelve patients had Type IV–V fracture according to Evans classification and underwent hemiarthroplasty were enrolled in the study. Patients operated using the posterolateral approach, that is, Group 1 (n=48), and patients operated using the transtrochanteric (transfracture) approach, that is, Group 2 (n=64), were compared in terms of dislocation, surgical duration, amount of blood transfusion, infection, mortality, and trochanteric nonunion. Factors that could affect the development of dislocation from the patient, surgery, and implant were also analyzed. Results: It was found that the rate of dislocation was statistically significantly higher in Group 1 in comparison to Group 2 (P<0.05). It was also observed that the surgical duration was statistically significantly shorter in Group 2 (P<0.05). It was found that the presence of a cognitive disorder, trochanteric nonunion, and use of posterolateral surgical approach resulted in a statistically significant increase in the rate of dislocation (P<0.05). Conclusion: Transtrochanteric (transfracture) approach is an effective method for minimizing possible complications following hemiarthroplasty, especially dislocation. Keywords: hip fractures, bipolar hemiarthroplasty, elderly, dislocation